PREDISCHAGE LUNG ULTRASOUND AS A PREDICTOR OF REHOSPITALIZATION OR MORTALITY ACUTE HEART FAILURE PATIENTS - Mirhansyah Perdana Hutasuhut, Zulfikri Mukhtar1&Teuku Bob Haykal (International Journal of Research Science and Management, 2020)
Backgroud: Persistent congestion is a major cause of rehospitalization in patients with acute heart failure (AHF). Lung Ultrasound (LUS) is an easy and valid examination in assessing pulmonary congestion. The number of B-lines correlates very strongly with the amount of extravascular lung fluid (EVLW). The aim of this study is to determine if LUS pre-discharge can predict rehospitalization or mortality. Methods: This single centered cohort study included 127 consecutive AHF patients. LUS on 28 antorolateral chest wall segment was done double blindly before discharging the patient to calculate the B-line. Clinical data, Composite Congestion Score (CCS) and echocardiography were collected. Cox proportional hazard regression analysis was performed to assess the independent predictor of rehabilitation or mortality during 120 days of observation. Results: The patients were 57.4 ± 7.8 years old, most were male (66.9%), with LV EF 36.7 ± 7.2%. The etiology of heart failure was caused by coronary heart disease (56.7%) and hypertensive heart disease (40.9%). The median number of B-lines was 24 (15 - 39). Hospitalization or death occurred in 43 patients (33.8%) during the median observation of 120 days (73-120). Patients with B-line pre-discharge ≥30 had a lower mean survival (log rank X2 48.14; p <0.001). In multivariate analysis, B-line pre-discharge ≥30 was the strongest independent predictor of rehabilitation or mortality (HR 4.71; 95% CI 2.15 - 10.32). Other independent predictors are Composite Congestion Score (CCS) ≥ 3 (HR 4.26; 95% CI 2.07 - 8.77) and NYHA functional class III (HR 2.87; 95% CI 1.49 - 5, 53). Conclusion: Persistent pulmonary congestion in AHF patients as assessed by B-line pre-discharge ≥30 is a strong independent predictor of rehospitalization or mortality. LUS could potentially help to guide the timing of discharge from AHF hospitalization, the follow-up scheduling and the therapy tailoring. Further randomized clinical studies are needed to definitely support the routine use of LUS.